A matlab toolbox for subband adaptive filtering - Lee, Celestine Si Hui. (2010)
In the 21st century, the rapid advancement of technology has allowed for many applications to tap on the benefits of enhanced sound quality. This necessitates the need for researchers to explore ways to perform filtering so as to remove disturbance of noise statics or any unwanted signals. Such unwanted signals usually originate from the equipment itself, or from the surrounding environment.